The Evolution of Energy Awareness in Hungary: Examining Consumer Awareness, Attitudes and Individual Responsibility in the Context of the Energy Crisis - Fűrész, Ágnes; Szeberényi, András; Kovács, Mátyás Imre (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
For decades, energy consumption—much like personal finance—was regarded as a low-involvement issue, receiving limited attention from the public. Only recent global disruptions, particularly the energy crisis, have prompted a shift in consumer perceptions. The crisis has underscored the unsustainability of prior consumption habits and exposed the vulnerability of energy systems. In response, an increasing number of consumers are demonstrating interest in energy awareness, sustainable behavior, and the potential of renewable energy sources. Although resistance to renewables remains, this is often rooted in insufficient education and a lack of intergenerational engagement with responsible energy use. In some population segments, energy is still not perceived as a value. This study investigates how the energy crisis has influenced consumer awareness and behavior in Hungary. Specifically, it explores the emergence and levels of energy awareness, the internal (e.g., environmental values, personal responsibility) and external (e.g., financial pressure, informational access) motivators driving behavioral change, and evolving attitudes toward renewable energy. It also examines whether consumers perceive a relationship between energy awareness and the crisis. Furthermore, the study offers recommendations on how artificial intelligence can be utilized to promote energy-conscious behavior through tailored educational interventions and decision-support tools.